Conservation status and distribution pattern of the Indus River Dolphin in River Beas, India - MOHD SHAHNAWAZ KHAN; ANJANA PANT (Biodiversitas Journal of Biological Diversity, 2014)
Khan MS, Pant A. 2014. Conservation status and distribution pattern of the Indus River Dolphin in River Beas, India. Biodiversitas 15: 75-79. Decline in the populations of Indus River Dolphins Platanista gangetica minor throughout its range of distribution and a perception that it is a 'keystone species' for riverine ecosystem stirred the idea of proposed study. Deficiency of baseline data on its distribution and ecology is a major constraint that this (only known sub-population in India) species’ conservation is facing in the country. Thus to ascertain its conservation status and distribution pattern, the study was conducted between December 2010 to June 2012. During the study, three schools of dolphins have been identified, one each along Beas bridge-Gagdewal; Baguwal-Dhunda and Karmowala-Harike that comprised of adult, sub-adult and calves. The occurrence dolphins was found attributed to preferred habitat features such as deep pools, slow water current, abundant prey base and low disturbance.